Pengelolaan Sumberdaya Pesisir Dan Laut Melalui Kearifan Lokal Di Mukim Mane Kecamatan Muara Batu Kabupaten Aceh Utara - Agussabti Agussabti; Adli Waliul Perdana; Indra Indra (Jurnal Agrisep, 2016)
Aceh has a lot of local wisdom in managing coastal dan marine resources.This research is aimed to (1) investigate form of local wisdom and tradition in Mukim Mane in managing coastal resources, (2) analyzing organization and policy who supervise the management of coastal resources through local wisdom and (3) analyzing strategy to strengthen societys local wisdom in managing coastal resources.This research was held in Mukim Mane Muara Batu District North Aceh. The method used is survey method with qualitative approach. The informants are Imum Mukim, Panglima Laot Lhok, fisherman, and local society. The result showed that the forms of coastal resources management are (1) the existance of prohibition day to sail, (2) taking care of other fisherman while sailing, (3) regulation to not cut down the mangroove forest (4) keeping the coral reefs (5) keeping the cleanliness of estuary and beach. The organization and policy who supervise the running of local wisdom in Mukim Mane are Panglima Laot and Aceh Qanuns. Strategies that can be done to strengthen local wisdom are by (1) incresing the role sinergy among government, college, panglima laot, and society and (2) developing the coastal society through cooperation, social unity, media, work relation pattern, and awareness about the importance of environment.